2021
DOI: 10.1016/j.toxcx.2021.100070
|View full text |Cite
|
Sign up to set email alerts
|

Mutual enlightenment: A toolbox of concepts and methods for integrating evolutionary and clinical toxinology via snake venomics and the contextual stance

Abstract: Snakebite envenoming is a neglected tropical disease that may claim over 100,000 human lives annually worldwide. Snakebite occurs as the result of an interaction between a human and a snake that elicits either a defensive response from the snake or, more rarely, a feeding response as the result of mistaken identity. Snakebite envenoming is therefore a biological and, more specifically, an ecological problem. Snake venom itself is often described as a “cocktail”, as it is a heterogenous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 168 publications
(220 reference statements)
0
32
0
Order By: Relevance
“…In these cases, it is assumed that the likelihood of ion selection for MS/ MS sequencing is higher for abundant peptides, and that the number of peptide identifications (normalised to protein size, since larger proteins generally give rise to more tryptic peptides), can provide a surrogate measure for the abundance of the parent protein. However, of particular importance in the venomics field, where a comprehensive sequence database is missing, quantification is biased toward successful peptide identifications (Calvette et al, 2021).…”
Section: Relationship Between Toxin Diversity and Protein Family Abun...mentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, it is assumed that the likelihood of ion selection for MS/ MS sequencing is higher for abundant peptides, and that the number of peptide identifications (normalised to protein size, since larger proteins generally give rise to more tryptic peptides), can provide a surrogate measure for the abundance of the parent protein. However, of particular importance in the venomics field, where a comprehensive sequence database is missing, quantification is biased toward successful peptide identifications (Calvette et al, 2021).…”
Section: Relationship Between Toxin Diversity and Protein Family Abun...mentioning
confidence: 99%
“…Venom proteomes of snakes have been published with increasing frequency since 2004 (Juárez et al, 2004), with a review published in late 2017 of 132 snake species characterised up to that point (Tasoulis and Isbister, 2017). Individual snake venoms consist of three to approximately 20 different recognised toxin protein families (Sanz et al, 2019;Calvette et al, 2021;Sunagar et al, 2021), made up from a total pool of 57 protein families so far reported in published snake venom proteomes. This total includes a number of regulatory proteins and low abundance protein families of unknown functional or biological significance.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research on the venoms of pompilids offers tantalizing hints at what we may yet discover, but there is clearly much work yet to be done. For some time now the gold standard approach to determining venom composition has required a combination of mass spectrometric proteomics and venom gland transcriptomics [145,146]. None of the studies that have applied mass spectrometry to pompilid venoms have been able to make use of accompanying transcriptomes [142,144,147,148].…”
Section: Discussionmentioning
confidence: 99%
“…A properly assembled and qualitycontrolled transcriptome from the same species (ideally the same individual) as the venom being analyzed gives much greater confidence that the proteomics results will be complete and accurate. In turn the proteomics help to validate which transcripts in the assembly are genuinely present in the venom gland and translated into proteins [145,146]. It is also important to consider the potential role of toxins that are not proteins or peptides.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Integration and contextualization of conceptual frameworks from ecological venomics and clinical toxinology can be mutually enlightening if snakebite envenoming is analyzed from an ecological stance. 23 Hence, identifying the specific pressures that tailored the composition and bioactivities of venoms across snake clades may have implications for the clinical treatment of human envenomings. 24 27 …”
Section: Introductionmentioning
confidence: 99%